The Eight and a Half Year Journey of Undiagnosed AD: Gene Sequencing and Funding of Advanced Genetic Testing Has Led to Hope and New Beginnings - Gozes, Illana; Patterson, Marc C.; Van Dijck, Anke; Kooy, R. Frank; Peeden, Joseph N.; Eichenberger, Jacob A.; Zawacki-Downing, Angela; Bedrosian-Sermone, Sandra (Frontiers in Endocrinology, 2017)
Background: Activity-dependent neuroprotective protein (ADNP) is one of the most prevalent de novo mutated genes in syndromic autism spectrum disorders, driving a general interest in the gene and the syndrome. Aim: to provide a detailed developmental case study of ADNP p.Tyr719* mutation toward improvements in 1] diagnostic procedures, 2] phenotypic scope, and 3] interventions. Methods: Longitudinal clinical and parental reports. Results: Alexi Sienna Downing (currently 11-year-old) had several rare congenital anomalies including imperforate anus that was surgically repaired at two days of age. Her findings were craniofacial asymmetries, global developmental delay, autistic-behaviors (loss of smile and inability to make eye contact at the age of 15 months) and slow thriving as she gradually matures. Comprehensive diagnostic procedures at 3 years resulted in no definitive diagnosis. With parental persistence, Alexi began walking at 3.5 years (skipping crawling). At the age of 8.5 years, Alexi was subjected to whole exome sequencing, compared to the parents and diagnosed as carrying an ADNP p.Tyr719* mutation, a causal recurring mutation in ADNP (currently ~17/80 worldwide). Brain magnetic resonance imaging (MRI) demonstrated mild generalized cerebral volume loss with reduced posterior white matter. Alexi is nonverbal, communicating with signs and word approximations. She continues to make slow but forward developmental progress, and her case teaches newly diagnosed children within the ADNP kids Research Foundation. Conclusions: This case study emphasizes the importance of diagnosis and describes, for the first time, early motor intervention therapies. Detailed developmental profile of selected cases leads to better treatments.